Photoluminescent Properties of Red-emitting AlPO4:Cr3+ Phosphor for Plant Growth LEDs - Manh Trung, Tran; Tu, Nguyen; Quang, Nguyen Van; Trung, Do Quang; Huy, Pham Thanh (VNU Journal of Science: Mathematics - Physics, 2021)
In this study, red-emitting AlPO 4 :Cr 3+ phosphors have been successfully synthesized by a facile sol-gel method. The Tanabe–Sugano diagram demonstrates that the surrounding sites of Cr3+ ions has a high crystal field with Dq/B=2.47. The sharp 694-nm peak on the PL of AlPO 4 :Cr 3+ phosphor could be attributed to the 2 E→ 4 A 2 electron transition of Cr 3+ ions. The AlPO 4 :0.3%Cr 3+ phosphor presents the highest PL intensity, then a purple LED prototype is obtained by coating the optimum powder on a UV LED chip. The color coordinates (0.2412, 0.1330) of the purple LED prototype implies that AlPO 4 :Cr 3+ phosphors are promosing to be used as deep red phosphor powder for horticulture LED lighting.